An exploratory approach to capture interpersonal synergies between defenders in football - Milho, J. (2018)
Collective behaviors in football may result from players forming inter¬personal synergies that contribute to performance goals. Due to the huge number of variables that continuously constrain players’ behavior during a game, the way that these synergies are formed remain unclear. In team sports such as football, a common effective defensive tactical strategy is one in that defending players “fill” the space between themselves, disturbing the attackers intentions to get closer to the goal and score. To assemble such situations, we hypothesized that the defenders create a functional synergy, which occurs when components of a system behave as a whole contributing to the development of a specific task (Kelso, 2009). Supported on a previous research in Rugby Union (Passos et al., 2017), we postulate that synergies are—mechanisms that substantiate interpersonal coordination in team sports of Football. It is relevant to state that a general feature of coordination is the mutual dependency among system components (e.g., defenders), which led them to behave (e.g., play) as a whole (Kugler and Turvey, 1987; Kelso, 2009). The creation of a synergy is grounded on a comple¬mentarity between variability and stability, which means that some defending player’s (as components of a system) must vary the manner they interact to stabilize specific performance variables (Black et al., 2007; Passos et al., 2017). On this exploratory study, our aim was to quantify interpersonal synergies in team sport of football, in particular, to quantify dyadic interpersonal synergies between the four field defenders that formed the defensive squad of a football team. We hypothesized that neighboring defending players adjust their relative positions to stabilize an interpersonal distance and as such create interpersonal synergies.